Peran Citra Destinasi Berkearifan Lokal Memediasi Atribut Destinasi dan Kualitas Layanan Terhadap Niat Berkunjung Kembali - Ni Putu Khrisnia Suandari; Ni Nyoman Kerti Yasa; I Putu Gde Sukaatmadja (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2023)
The aim of this research is to explain the role of destination image with local wisdom in mediating the influence of destination attributes and service quality on intention to return to tourist villages in Buleleng Regency. The population of this research is domestic tourists who have visited tourist villages in Buleleng Regency. The sample size used was 115 domestic tourists using a purposive sampling method. The analysis technique used is Path Analysis using SEM-PLS. The research results show that destination attributes have a positive and significant effect on the image of a destination with local wisdom and intention to visit again. Service quality has a positive and significant effect on the image of a destination with local wisdom and intention to visit again. Likewise, the image of a destination with local wisdom has a positive and significant effect on intention to visit again. Furthermore, destination image with local wisdom is able to partially mediate the influence of destination attributes and service quality on intention to revisit.